2021
DOI: 10.3389/fphar.2021.565748
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nrf2-Mediated Oxidative Stress Response Signaling Pathways as New Therapeutic Strategy for Pituitary Adenomas

Abstract: Oxidative stress and oxidative damage are the common pathophysiological characteristics in pituitary adenomas (PAs), which have been confirmed with many omics studies in PA tissues and cell/animal experimental studies. Nuclear factor erythroid 2 p45-related factor 2 (Nrf2), the core of oxidative stress response, is an oxidative stress sensor. Nrf2 is synthesized and regulated by multiple factors, including Keap1, ERK1/2, ERK5, JNK1/2, p38 MAPK, PKC, PI3K/AKT, and ER stress, in the cytoplasm. Under the oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 151 publications
(200 reference statements)
1
24
0
Order By: Relevance
“…In the present study, gastrodin upregulated the phosphorylation levels of AMPK, Nrf2 and the expression of HO-1, which was consistent with the previous study aforementioned. Previous studies also reported that AMPK and Nrf2 can mediate fatty acid oxidation and reduce oxidative stress, respectively (47,48). The activation of AMPK/Nrf2 signaling was previously found to improve lipid metabolism and attenuated oxidative stress in renal tissues of mice with type 2 diabetes-induced nephropathy (25,49).…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, gastrodin upregulated the phosphorylation levels of AMPK, Nrf2 and the expression of HO-1, which was consistent with the previous study aforementioned. Previous studies also reported that AMPK and Nrf2 can mediate fatty acid oxidation and reduce oxidative stress, respectively (47,48). The activation of AMPK/Nrf2 signaling was previously found to improve lipid metabolism and attenuated oxidative stress in renal tissues of mice with type 2 diabetes-induced nephropathy (25,49).…”
Section: Discussionmentioning
confidence: 90%
“…However, when the system is oxidatively-stressed, the Nrf2 from the cytoplasm is translocated to the nucleus, where it binds to the ARE of the gene coding for antioxidant proteins, activating a cascade of reaction which help to curb the oxidative pressure on the cells ( Saha, Buttari, Panieri, Profumo, & Saso, 2020 ). Studies have shown with consensus evidence that decrease in Nrf2 activities invariably contributes to oxidative stress and cardiovascular diseases such as hypertension ( Serafini et al, 2020 , Zhan et al, 2021 ). Considering that some antioxidant peptides also exhibit antihypertensive properties, and that oxidative stress is implicated in hypertension ( Griendling et al, 2021 ), the investigation of Keap-1/Nrf2 signaling pathway (the activation or upregulation the expression and translocation of nuclear Nrf2) and gene expression of antioxidant enzyme activities in peptide-treated SHR is recommended for future studies.…”
Section: Emerging Mechanisms Of Blood Pressure-lowering By Bioactive ...mentioning
confidence: 99%
“…In addition, mitochondrial proteins can regulate numerous signalling pathway networks and cellular behaviours, with this organelle being involved in an extensive range of diseases, including tumorigenesis (116). Molecular network studies have revealed that mitochondrial dysfunction, oxidative stress and mitochondria-mediated ROS-mitogen-activated protein kinase (MAPK) signalling abnormality are significantly associated with the pathogenesis of PitNETs (69,70,72,(117)(118)(119)(120).…”
Section: Cellular Bioenergeticsmentioning
confidence: 99%
“…Furthermore, mitochondrial dysfunction has been described showing morphological and functional changes, such as bigger mitochondria with irregular swelling and fragmented cristaes ( 124 ). An activation of the nuclear factor erythroid 2 like 2 (Nrf2) pathways, a main regulator of oxidative stress response along with oxidative damage signal reduction, have been reported during PitNET development, which might provide cellular survival advantages ( 120 , 124 ). Indeed, elevated mitophagy and mitochondrial dysfunction may favour resistance to chemotherapy in the pituitary GH3 cell line ( 131 ).…”
Section: Introductionmentioning
confidence: 99%